The participation in global value chain o f supporting industry the case o f Vietnam - Bang, Yen Hoa (H. : ĐHQGHN, 2020)
The trend of trade liberalization and international economic integration allow all levels of economy to actively participate in the international trade through production networks and global value chains. Every country want to join into the global value chain and achieve high added value in the chain, and Vietnam in general and supporting industry in particular needs to develop the beginning stage as well as the final stages of the value chain, which is engaged in the field of research and development of intellectual property, trademarks and trade. That is also the natural choice to get rid of backwardness and dependence.